Safety and immunogenicity of a recombinant double-mutant heat-labile toxin derived from enterotoxigenic Escherichia coli in healthy Bangladeshi adults delivered by three different routes - Bhuiyan, Taufiqur Rahman; Khanam, Farhana; Basher, Salima Raiyan; Dash, Pinki; Chowdhury, Mohiul Islam; Haque, Shahinur; Harun, Nabila Binte; Akter, Aklima; Karmakar, Polash Chandra; Hakim, Al; Amin, Shaheena; Kamruzzaman, Mohammad; et al. (Frontiers in Bacteriology, 2025)
IntroductionEnterotoxigenic Escherichia coli (ETEC) is a common cause of acute watery diarrhea in areas lacking access to clean water, sanitation, and hygiene. This Phase 1 trial measured the safety and immunogenicity of double-mutant heat-labile enterotoxin (dmLT) of ETEC in healthy adults in Bangladesh, where ETEC is endemic.MethodsFive cohorts of 15 participants each were enrolled and randomized 4:1 to receive vaccine dmLT or placebo (12 vaccine and 3 placebo recipients per cohort). The 3 oral or sublingual doses of 5 µg or 25 µg dmLT were administered 2 weeks apart; the 2 intradermal doses of 0.3 µg dmLT were administered 3 weeks apart. Safety was assessed by collecting solicited and unsolicited adverse events. The immune responses measured included dmLT-specific serum IgA and IgG, serum toxin neutralizing antibody, dmLT-specific IgA and IgG antibody secreting cells (ASC), and IgA and IgG antibodies in lymphocyte supernatant (ALS).ResultsAll doses of dmLT delivered by different routes were well tolerated; adverse events were few, mild, and transient. Serum, ALS, and ASC IgA and IgG responses, as well as LT neutralizing antibody responses, were greatest among recipients of 25 µg oral and 0.3 µg intradermal doses. In contrast, sublingual dosing induced modest responses; there was virtually no serum antibody response to 5 µg sublingual dose and only sporadic ALS and ASC responses with 5 µg and 25 µg doses.DiscussionIn conclusion, dmLT was well tolerated, and immune responses were dependent on dmLT dose and route of administration. The encouraging tolerability and immunogenicity results further highlight dmLT’s potential not only as a vaccine but also as an adjuvant as reported by others or as a candidate vaccine antigen.Clinical Trial Registrationwww.clinicaltrials.gov, identifier NCT03548064.